The Vaccine Uptake Continuum: Applying Social Science Theory to Shift Vaccine Hesitancy - Rachael Piltch-Loeb (Vaccines, 2020)
Vaccines are the optimal public health strategy to prevent disease, but the growing anti-vaccine movement has focused renewed attention on the need to persuade people to increase vaccine uptake. This commentary draws on social and behavioral science theory and proposes a vaccine uptake continuum comprised of five factors: (1) awareness of the health threat; (2) availability of the vaccine; (3) accessibility of the vaccine; (4) affordability of the vaccine; and (5) acceptability of the vaccine to effectively approach this rising challenge.